Derivation of cutoffs for the Elecsys® amyloid β (1–42) assay in Alzheimer's disease. Issue 1 (10th August 2018) - Shaw, Leslie M.; Waligorska, Teresa; Fields, Leona; Korecka, Magdalena; Figurski, Michal; Trojanowski, John Q.; Eichenlaub, Udo; Wahl, Simone; Quan, Marian; Pontecorvo, Michael J.; Lachno, D. Richard; Talbot, Jayne A.; et al.
Abstract: Introduction: An Elecsys® Amyloid β (Aβ [1–42]) immunoassay cutoff for classification of patients with Alzheimer's disease was investigated. Methods: Cerebrospinal fluid samples collected from patients with mild‐to‐moderate Alzheimer's disease were analyzed by Elecsys® immunoassays: (1) Aβ (1–42), (2) total tau, and (3) phosphorylated tau. Cutoffs (Aβ [1–42] and ratios with tau) were estimated by method comparison between AlzBio3 ( n = 206), mixture modeling ( n = 216), and concordance with florbetapir F 18 imaging‐based classification ( n = 75). Results: A 1065‐pg/mL (95% confidence interval: 985–1153) Elecsys® Aβ (1–42) cutoff provided 94% overall percentage agreement with AlzBio3. Comparable cutoff estimates (95% confidence interval) were derived from mixture modeling (equally weighted: 1017 [949–1205] pg/mL; prevalence weighted: 1172 [1081–1344] pg/mL) and concordance with florbetapir F 18 imaging (visual read: 1198 [998–1591] pg/mL; automated: 1198 [1051–1638] pg/mL). Discussion: Based on three approaches, a 1100‐pg/mL Elecsys® Aβ (1–42) cutoff is suitable for clinical trials with similar populations and preanalytical handling. Highlights: Biomarkers can facilitate appropriate patient recruitment into clinical trials. Amyloid beta measurement can aid the identification of amyloid‐positive patients. Similar cutoff estimates were derived by three different approaches.